Board compensation practices and agency costs of debt - Ertugrul, Mine; Hegde, Shantaram (Journal of Corporate Finance, 2008)
Extant theory and empirical evidence indicate that equity-based compensation can align the interests of managers with those of shareholders, but it has a side effect of aggravating bondholder-shareholder conflicts by increasing managers' risk-shifting incentives. Recent evidence confirms that extending equity-based compensation to outside directors also is effective in aligning their interests with those of shareholders, but its adverse effects on the debt-related agency problems are unknown. In this paper, we examine how stock and stock option compensation for outside directors affects corporate bond yields in the secondary market. Our results show that the greater the ratio of outside directors' stock and option compensation to total compensation, the lower the average yield spreads on the firms' outstanding bonds, with stock compensation having a larger impact than option compensation. Further, the effect of equity-based compensation on yield spreads is stronger for firms with lower-rated debt.